An Electrostatic Spinning Technology with Improved Functionality for the Manufacture of Nanomaterials from Solutions - Marek Pokorny; Jindrich Novak; Jiri Rebicek; Jan Klemes; Vladimir Velebny (Nanomaterials and Nanotechnology)
The last decade has seen an extensive development of the field of nanomaterials which are currently being used in their first commercial applications. This rapid develop‐ ment is necessarily connected with certain technological demands. This paper describes a technology for the manufacture of nanomaterials from solutions by electro‐ static spinning or spraying. Although this method has been well known since the last century, there are still only a few high-quality devices that can be used for the research of new nanomaterials. The main reason for this is that the process of nanomaterials manufacturing is influenced by numerous processing parameters which need to be properly regulated, and furthermore all device compo‐ nents must be resistant to interference from high voltage. The technological requirements are thus stringent. More‐ over, such a device must be multifunctional, compact and affordable. This paper describes the technical aspects of a unique laboratory device, i.e., device modules and central control, measured processing parameters, and their effect on the produced materials. The developed laboratory device meets the most demanding criteria for a nanotech‐ nological laboratory device and helps facilitate and speed up the research and development of new nanomaterials produced in high electrostatic field.